A Randomized Controlled Trial Comparing Dexmedetomidine and Fentanyl as Adjuvants to Epidural Labour Analgesia - Dr. P. G. Raghavendra, Dr. Sahana P R, Dr. Anuja (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Dexmedetomidine (DEX), an α2-adrenergic agonist, has been proposed as anepidural adjuvant to local anesthetics for labour analgesia with potential advantages over opioids such as fentanyl (FEN).